FUZZY MATHEMATICAL PHILOSOPHY - Vasylevych, Leonid F. (Educological discourse, 2014)
The work gives arguments that philosophy as a science is supposed to have its mathematical apparatus. And of many mathematical apparatuses the most adequate one is believed to be the theory of fuzzy and fuzzy logic. It is recommended to include a course of Theory of fuzzy and fuzzy logic into university curriculum for the students majoring in philosophy.